Presumptive injection-site sarcoma in a white tiger (Panthera tigris tigris): A case report - Moosavian, H; Esmaeilzadeh, H; Fazli, M; Thompson, CA; Farajzadeh, A (Journal of the Hellenic Veterinary Medical Society, 2024)
A 6-year-old female White Tiger (Panthera Tigris Tigris) was presented with a history of a recurrent ulcerating mass on the right lumbar wall which initially, was removed by surgery one year before presentation. Cytological and histological findings were consistent with a cutaneous injection site sarcomas. Immunohistochemistry results revealed that the neoplastic cells were strongly positive for vimentin and weakly positive for alpha-smooth muscle actin (SMA), but negative for Cytokeratin AE1/AE3, s100, and Desmin. Positive staining for vimentin and SMA is consistent with myofibroblast reactivity and reflects a continuous inflammatory response seen in feline injection-site sarcomas. Feline injection-site sarcomas are the most serious adverse effect following injection of the vaccine or some other pharmaceutical substances and should be considered in the differential diagnosis of skin swelling in injection sites in the Felidae family. Limited data are available for these tumors in animals outside of domesticated cats. To the best of our knowledge, there exists no available published information on the injection-site sarcoma in tigers. Similar to domestic felids, this case highlights the importance of considerations and management options in vaccination schedules for the reduction of sarcoma risk in wild felids.